Outcomes of non-metastatic gestational trophoblastic neoplasia: Twelve year experience from a Northern Thailand Tertiary Care Center - Prapaporn Suprasert (2018)
Gestational trophoblastic neoplasia (GTN) is the malignant form of gestational trophoblastic disease. In non-metastatic GTN, the outcomes of treatment are impressive with methotrexate (MTX) or actinomycin D. We retrospectively reviewed the outcomes of non-metastatic GTN treated at our center from January, 1999 to December, 2013. One hundred and nine patients were recruited to the study. The median age was 33.1 years and over 90% were referral cases. Abnormal vaginal symptoms developed in 37.6% while 56.4% were asymptomatic. The most common antecedent pregnancy was a complete mole (92.7%) with the median interval time from antecedent pregnancy to GTN development being 2.0 months. The median pretreatment B-hCG was 5,624 mIu/ml. The most common first line treatment was methotrexate (MTX) and folinic acid (91.7%) followed by weekly MTX (4.6%), etoposide+ MTX+actinomycin D (EMA) (2.8%), and actinomycin D (0.9%), with the median number of cycles at 5.0. The positive response to first line chemotherapy was 73.8%. The patients were given subsequent chemotherapeutic regimens after resistance to the first line therapy and showed a final remission rate of 89.9%.The significant factor that was frequently found in patients who were non-responders to the first line treatment was a hysterectomy procedure. Two patients developed lung metastasis and brain metastasis at one and four years after the first treatment, respectively. In conclusion, the outcomes of non-metastatic GTN were excellent. However, the patients need long term follow up due to the possibility of developing multiple organ metastases.